2014
DOI: 10.36076/ppj.2014/17/e263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methodologic Quality of Randomized Trials of Interventional Techniques: Development of an Interventional Pain Management Specific Instrument

Abstract: Background: A major component of a systematic review is an assessment of the methodological quality and bias of randomized trials. The most commonly utilized methodological quality assessment and bias assessment for randomized trials is by the Cochrane Review Group. While this is not a “gold standard,” it is an indication of the current state-of-the-art review methodology. There is, however, no specific instrument to assess the methodological quality of manuscripts published for interventional techniques. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Of the 6 manuscripts meeting inclusion criteria [ 25 , 31 , 33 , 37 , 38 , 40 ], there was only one placebo-controlled RCT [ 25 ]. Appendix Tables 4 and 5 show the methodologic quality assessment and risk of bias of the one RCT utilizing the Cochrane review criteria and the IPM-QRB criteria respectively [ 27 , 28 ]. Assessment by the Cochrane review criteria and IPM-QRB of this RCT showed high quality [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 6 manuscripts meeting inclusion criteria [ 25 , 31 , 33 , 37 , 38 , 40 ], there was only one placebo-controlled RCT [ 25 ]. Appendix Tables 4 and 5 show the methodologic quality assessment and risk of bias of the one RCT utilizing the Cochrane review criteria and the IPM-QRB criteria respectively [ 27 , 28 ]. Assessment by the Cochrane review criteria and IPM-QRB of this RCT showed high quality [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative analysis was performed utilizing a modified approach for the grading of evidence [ 28 ] with moderate (level II) evidence from one relevant high-quality RCT and 5 relevant moderate-quality observational studies. All of the studies consistently showed improvement in patients undergoing neurolysis at 6 months and one-year follow-up periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of evidence for each treatment class was graded from I-III as detailed in (Table 1) and a degree of recommendation was provided on a scale from A to D, or as insufficient (I), according to the United States Preventive Services Task Force (USPSTF) criteria (Table 2). [23][24][25]…”
Section: Evaluation and Analysis Of Evidencementioning
confidence: 99%
“…The quality of each individual article used in this analysis was assessed by Cochrane review (76) criteria and Interventional Pain Management techniques--Quality Appraisal of Reliability and Risk of Bias Assessment (IPM-QRB) for randomized trials (77).…”
Section: Risk Of Bias Of Individual Studiesmentioning
confidence: 99%